2022
DOI: 10.1007/978-3-031-12224-8_11
|View full text |Cite
|
Sign up to set email alerts
|

Parenthood: Disrupting the Intergenerational Transmission of Social Disadvantage

Abstract: This chapter examines parenthood, arguably one of the most significant life course transitions in an individual’s life with consequences not just for the adults involved, but also children whose developmental outcomes are strongly influenced by parenting styles, practices and resources. We examine how parenting practices are influenced by social disadvantage, including disadvantage at the individual, family and community levels, arguing that this influence is complex and multi-directional, with reciprocal asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 136 publications
0
2
0
Order By: Relevance
“…For instance, McKee et al’s (2021) latent profile analysis found that compared to low-income families, high income families were less likely to be a member of an emotion dismissing profile. Parents with limited resources and support likely experience increased stressors and difficulties managing their emotions, therefore, emotion dismissing parenting ( Shaffer et al, 2012 ; Burke and Dittman, 2022 ). Furthermore, parents who have a higher education may be more likely to receive opportunities and resources that educate them on more optimal parenting approaches.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, McKee et al’s (2021) latent profile analysis found that compared to low-income families, high income families were less likely to be a member of an emotion dismissing profile. Parents with limited resources and support likely experience increased stressors and difficulties managing their emotions, therefore, emotion dismissing parenting ( Shaffer et al, 2012 ; Burke and Dittman, 2022 ). Furthermore, parents who have a higher education may be more likely to receive opportunities and resources that educate them on more optimal parenting approaches.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, McKee et al 's (2021) latent profile analysis found that compared to low-income families, high income families were less likely to be a member of an emotion dismissing profile. Parents with limited resources and support likely experience increased stressors and difficulties managing their emotions, therefore, emotion dismissing parenting (Shaffer et al, 2012;Burke and Dittman, 2022). Furthermore, parents who have a higher education may be more likely to receive opportunities and resources that educate them on more optimal parenting approaches.…”
Section: Construct Validity and Reliability Of The Profilesmentioning
confidence: 99%